Double Stratified Mixed Convective Flow of Couple Stress Nanofluid past Inclined Stretching Cylinder Using Cattaneo-Christov Heat and Mass Flux Model - Wubshet Ibrahim; Gosa Gadisa (Advances in Mathematical Physics)
In this exploration, a double stratified mixed convective flow of couple stress nanofluid past an inclined stretching cylinder using a Cattaneo-Christov heat and mass flux model is considered. The governing partial differential equation of the boundary layer flow region is reduced to its corresponding ordinary differential equation using a similarity transformation technique. Then, the numerical method called the Galerkin finite element method (GFEM) is applied to solve the proposed fluid model. We performed a grid-invariance test or grid-convergence test to confirm the convergence of the series solution. The effects of the different noteworthy variables on velocity, temperature, concentration, local skin friction, local Nusselt number, and local Sherwood number are analyzed in both graphical and tabular forms. We have compared our result with the existing results in the literature, and it is shown that GFEM is accurate and efficient. Moreover, our result shows that the velocity field is retarded when the angle of inclination enhances and the heat transfer rate is reduced with larger values of the curvature of the cylinder.